Strategi Guru Dalam Memberikan Pemahaman Tauhid Kepada Anak Di TK Hubulwaton, Kecamatan Ranah Batahan, Kabupaten Pasaman Barat - Siti Haula (Humantech : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
This research is motivated by events in the field. that researchers look at the teaching and learning process to find out what strategies are given by the teacher in providing an understanding of monotheism to children and what obstacles are faced by teachers in teaching monotheism to children. This research is qualitative, the data collection technique is done by interview observation. While the data processing techniques that are carried out in writing use selecting or checking data, describing what is obtained and presenting. To find out the extent to which teachers provide the teachings of monotheism to children and the extent to which children understand that monotheism is prohibited and what is good, and how to overcome it. Based on the research conducted, the authors can conclude that the teacher's strategy in providing understanding of monotheism to children has been carried out, although it has not fully provided maximum results. This strategy that the teacher does is habituation, example, stories / stories, singing, playing, lecturing. and the obstacles faced by teachers in carrying out learning are the teacher's lack of understanding of monotheism, the teacher's lack of understanding of electronic goods